Recycling of treated alum sludge and glycerine pitch in the production of eco-friendly roofing tiles: Physical properties, durability, and leachability. (15th July 2022) - Teoh, Wei Ping; Chee, Swee Yong; Habib, Noor Zainab; Chok, Vui Soon; Lem, Kong Hoong; Looi, Sing Yan; Ng, Choon Aun
Abstract: Three different types of alum sludge, which are raw alum sludge (RAS), thermally activated alum sludge (TAAS) and pulverized alum sludge ash (PASA) were incorporated as filler in the production of novel roofing tiles. An oleochemical by-product, known as glycerine pitch (GP) was utilized as the alternative binder throughout this study. In the manufacturing process, 15–30% of alum sludge was mixed with specific proportion of GP and fine sand, molded via a compaction process, and heat cured at 165 or 195 o C for 24–72 h. The possible environment impacts that may be caused by the alum composition in the specimen had been investigated through leachate test. In addition, the physical properties achieved by the specimens, including the density, transverse breaking strength, water absorbability, permeability and porosity were also assessed. The highest mechanical strength of 2674.33 N was achieved by the specimen when 20% of binder and 80% of sludge-sand at 1:3 ratio was incorporated, while the least water uptake was determined when AS was utilized. The water resistivity of the specimen was further enhanced by introducing a coating layer derived from used cooking oil (UCO), which resulted in a low percentage of water absorption of 4.32%. The durability of the optimized specimen was investigated by observing the changes in the appearances and loss in mass upon the sulphate attack. Conclusively, the conservation of natural resources by recycling and reuse of multiple waste materials in the production of building materials is the predominant outcome of this research study. Highlights: Utilization of glycerine pitch as the main binder to produce roofing tiles. Incorporation of raw and treated alum sludge as the filler to produce roofing tiles. Adding used cooking oil to enhance strength and water resistivity of roofing tiles. Increasing the waste replacement extent by recycling multiple waste materials.